Teachers views about limitations / barriers of implementing teachers ‘evaluation system in Undergraduate dental education in Bangladesh (Update Dental College Journal, 2018)
Teachers are the main elements of dental education and naturally their performance has an essential role in health service efficiency. It is a series of activities and actions that are interconnected and relate to a specific purpose in the last two decades, the importance of teaching evaluation has been emphasized in higher education. Many medical and dental schools have searched for ways to effectively and constructively evaluate performances of their faculty members. The most common sources of evaluation data have been students, peers, and teachers themselves1. Teacher evaluation is often designed to serve two purposes- to measure teacher competence and to foster professional development and growth. The goal of any effective evaluation process must be growth of good teacher2. Everyone wants to see our teachers grow and help them maximize their potential. Therefore the process is not one of “Got You” but rather one of facilitating growth. One of the qualities we need to have as educational leaders is that of humility and we should want to see our teachers succeed3. This cross-sectional descriptive study was carried out among the teachers of three dental colleges of Dhaka city in last one year (2010-2011). Data were collected by convenience sampling. One public dental college and two private dental colleges were chosen according to the convenience of the researcher.34 teachers participated the study 34 (n-34) by semi structured self-administered questionnaire to explore their views regarding teacher’s evaluation in undergraduate dental education. All the answers were recorded by writing and checked at the end of the interview.Update Dent. Coll. j: 2018; 8 (2): 2-4